THE POSSIBLE ROLE OF MUMPS VIRUS INTHE DEVELOPMENT OF INSULIN DEPENDANTDIABETES MELLITUS - Taha, R.; D., Dawood; K., Mustafa (Iraqi Journal of Science, 2024)
Mumps is an acute viral illness associated with different types of complications,Pancreatitis is one of infrequent mumps complications followed by diabets mellitustype one in few cases. The present study was designed to determine whether arelationshipe exposure to mumps by natural infection or vaccination withMMRvaccine and diabetes type one.Seventy two patients with Insulin dependent diabetes mellitus exposed to mumps byvaccinor natural infection compared with ١٨ (healthy) age and sex matched controlwere included in this study . Blood samples were taken for investigation of Glutamicacid decarboxylasw antibody (GADA), Islet cell antibody (ICA) and Mumps IgGAntibody by using ELISA and immunoflorescent technique.Islet cell antibody was detected in ١٣ (١٨.١%) patients ٦ (٨.٣%) males and ٧ (٩.٧%)females. GADA was detected in ٤٥ patients (٦٤.٥%) ٢٤ males (٣٣.٣%) and ٢١(٢٩.٢%) females. Mumps IgG Antibody was found in ٢١ (٢٩.٢%) of patients